Historični seminar 14 - Žagar Karer, Mojca; Šter, Katarina (ZRC SAZU, Založba ZRC, 2021)
The volume Historični seminar 14 ('Historical Seminar 14'), issued in the time of transformed reality of what we knew and took for granted, draws attention to the fact that the image we cultivate of ourselves and our history may sometimes be too simplified to be entirely real. At first, the volume both revises already known chapters of Church history and introduces hitherto unknown ones. Simon Malmenvall's analysis of the characters of the noble martyrs Boris and Gleb, Jovan Vladimir, and Magnus Erlendsson shows how the stories of their martyrdom had a nation-building function. Celeste McNamara's article on Giovanni Barbarigo introduces the unusual and less well-known topic of seventeenth-century missions. Monika Deželak Trojar analyzes in detail Johann Ludwig Schönleben's German and Latin Lenten sermons. Aleš Maver's article discusses why Latin disappeared so quickly from Slovenian churches after the Second Vatican Council. On the other hand, the pre-modern religious practices of nature worshippers in Slovenia are discussed by Cirila Toplak. Modern times and also more political issues are examined by Tomaž Ivešić who focuses on the increase in ethnic tensions in Yugoslavia in the early 1970s, while Aleksandar Takovski traces the historical representation of heroic figures in four former Yugoslav countries.